Visualization for Information Retrieval based on Fast Search Technology - Mamoon H. Mamoon; Hazem M. El-Bakry; Amany Salama (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
The core of search engine is information retrieval technique. Using information retrieval system backs more retrieval results, some of them more relevant than other, and some is not relevant. While using search engine to retrieve information has grown very substantially, there remain problems with the information retrieval systems. The interface of the systems does not help them to perceive the precision of these results. It is therefore not surprising that graphical visualizations have been employed in search engines to assist users. The main objective of Internet users is to find the required information with high efficiency and effectiveness. In this paper we present brief sides of information visualization's role in enhancing web information retrieval system as in some of its techniques such as tree view, title view, map view, bubble view and cloud view and its tools such as highlighting and Colored Query Result.